A Modified Version of Generalized Standard Addition Method as Quantitative Determination of Lysineacetyl salicylate-Glycine Complex - Shams A. Nadhum (Journal of Global Pharma Technology, 2016)
The quantitative determination of lysine (Lys) and glycine ( Gly) in their complexes salts with aspirin was achieved using a modified version of the Generalized standard addition method ( GSAM)   that  aimed at the validation and standardization of analytical procedures with direct solid sample contain two types of amino acids without previous isolation. It was intended to separate aspirin quantitatively from them before determination by titration. It was intended to use spectrophotometry or titrimetric for determination of lysine and glycine. According to this method, two linear equations were solved to obtain the amounts of (Lys) and (Gly) by using two different wavelengths using  ninhydrin  as a color developing reagent in the spectrophotometric procedure, as it is the most selective among other coloring agent for spectrophotometric determination for amino acids. The high accuracy and precision of the results indicate that this method is simple, fast, precise and suitable to be used as a quality control procedure for analysis of commercial product (aspegic).Keywords: Aspirin, glacial acetic acid, glycine (as aspirin amino acid salt), Hydrochloric acid, lysine (as aspirin amino acid salt), ninhydrin,  perchloric acid, UV spectrophotometer.